Analisis Perilaku Masyarakat dalam Pengelolaan Sampah Rumah Tangga di Kel. Padang Bulan Selayang II, Lingkungan IV - Andini, Syarifah; Rahmah, Mawaddah; Siregar, Risbue; Hsb, Novita Annisah; Luahambowo, Kerin Sisca Octaviani (IAI Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to identify and explain how residents in Medan Selayang Sub-district, Padang Bulan Selayang II Urban Village, Neighbourhood IV manage household waste. The purpose of this descriptive qualitative case study method is to analyse people's behaviour in waste management as well as the elements that influence it, such as social, cultural, economic, and infrastructure aspects. It is expected that the results of the study will provide a deeper insight into the difficulties and opportunities in waste management in the neighbourhood. They will also provide suggestions to increase community awareness and involvement.